CO2Fix: An approach to assess CO2 fixation potential of CCU reaction pathways - Gasim Ibrahim (17032299) (2023)
In this work we present a simple, yet powerful, metric for estimating the potential of a CCU reaction pathway to fix CO2. The CO2Fix metric is determined by using a model that accounts for various process variables and parameters that influence the ability of the reaction to convert CO2 in addition to its propensity to produce CO2 through the energy requirements of the process. The CO2Fix metric in this work accounts only for the direct CO2 emissions and indirect CO2 emissions related to the reaction portion of a CCU process. We demonstrate the use of the model to estimate the CO2Fix in two case studies representing common CCU reactions: dry reforming of methane (DRM) and CO2 hydrogenation to methanol. When using natural gas-powered energy, and under the same process assumptions, the CO2Fix was estimated to be 1.1 and 3.9 for the DRM and CO2 hydrogenation reactions respectively. Other Information Published in: Computers & Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.compchemeng.2023.108398